Selection of agriculture sector as career developments and its relationship to student performance among undergraduate students in Faculty of Agriculture, UPM - Samri, Ahmad Jaki (2015)
Agriculture is the important sector in Malaysia which encompasses a broad field which include livestock, crop production, aquaculture, entrepreneurship and downstream sector related to agriculture. Currently, agriculture becomes the second largest contributor to the Gross Domestic Product (GDP). Universiti Putra Malaysia through Faculty of Agriculture plays a major role to find solution for current agriculture problems including producing human resources for producing trained individuals comprising of graduates who visionary and comparative in the agricultural sector. The career selection of the students will shape our future agriculture sector to ensure the continuation of contribution for national economic growth. The main objective of the study is to identify the selection of agriculture sector as career choice among undergraduate students in Faculty of Agriculture, UPM. The research is conducted using mixed method research. First, by distribution of the questionnaire among 234 students which are selected using stratified random sampling. The frequency, percentages, correlation and regression was calculated from the result of the questionnaire. Secondly, face to face interview was done from four different respondents. From the study, almost all students will involve in agriculture sector as the career choice after graduate from their study. This was represented from huge percentages of student who interest to work as self-employ in agriculture and government sector related to agriculture. Correlation analysis also has shown strong positive correlation between career developments in agriculture toward student performance.